MECHANISM OF WAVE - INDUCED FLOWS IN SWASH ZONE IN THE NHA TRANG BEACH, VIETNAM - Cuong, Nguyen Kim; My, Tran Van; Jean-Pierre, Lefebvre (Vietnam Journal of Marine Science and Technology, 2016)
This paper analyzed the measured and simulated data in the field survey in the Nha Trang beach in May 2013. The measurements in the surf and swash zones have been conducted. In order to address the quantification of the very shallow, highly turbulent flow in the swash zone, a high frequency micro profiler was deployed (Vectrino II, Nortek). In addition, a dam-break model to simulate process of wave propagation in the swash zone was developed and applied. It is confirmed that the numerical model reasonably reproduces the measured data. The height of water bore in the swash zone gets greater with the increase of offshore wave height. The results enable the estimation of the Reynolds stress component and Turbulent Kinetic Energy. Swash bed shear stresses play an important role in controlling the swash morphodynamic processes on sand and gravel beaches.